From Hashtags to Health: Evolving Themes in Women’s Digital Activism Across Global Contexts - Gasa, Frederik Masri; Ida, Rachmah; Wahyudi, Irfan; Angkawijaya, Yongkie; Bakhir, Norfarizah Mohd (Journal of Social Dynamics and Governance, 2026)
This study provides an overview of how the field of women’s digital activism has been evolving, through a mixed-method approach combining a systematic literature review (SLR) and bibliometric analysis. While digital platforms have emerged as important venues for women to advocate for their particular concerns, engage in collective mobilization, and contest various social injustices, analyses on the governance response to these phenomena are scarce in the literature. Following the PRISMA guidelines, we have analysed 30 indexed articles in Scopus published from 2011 to 2025. The VOSviewer software was applied for mapping the publishing trend, institution, countries/regions, academic fields, and intellectual clusters in the body of literature. Our findings demonstrate a significant acceleration in publications between 2023 and 2024, representing an expanding and more diversified research landscape in such topics as health activism, feminist perspectives to gender-based violence, and transnational networks in the Middle East and North Africa region. Yet, we also find a concentration of the literature within Western academia and Social Sciences scholarship, with insufficient research on the governance of digital platforms, state regulation, and the Sustainable Development Goals, in particular, SDG 5 (Gender Equality) and SDG 16 (Peace, Justice and Strong Institutions).